2015
DOI: 10.18632/oncotarget.4376
|View full text |Cite
|
Sign up to set email alerts
|

Halofuginone inhibits colorectal cancer growth through suppression of Akt/mTORC1 signaling and glucose metabolism

Abstract: The Akt/mTORC1 pathway plays a central role in the activation of Warburg effect in cancer. Here, we present for the first time that halofuginone (HF) treatment inhibits colorectal cancer (CRC) growth both in vitro and in vivo through regulation of Akt/mTORC1 signaling pathway. Halofuginone treatment of human CRC cells inhibited cell proliferation, induced the generation of reactive oxygen species and apoptosis. As expected, reduced level of NADPH was also observed, at least in part due to inactivation of gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 45 publications
4
45
0
1
Order By: Relevance
“…For example, ATS has anti-proliferation effects on human breast cancer [7], neuroblastoma [8] and ishikawa endometrial cancer [9]. HF also has the ability to inhibit the proliferation of human colorectal cancer cells [10], multiple myeloma cells [11], and liver cancer cells [12]. According to the history of using the formula of Qinghao and Changshan in TCM, we hypothesize that HF and ATS could exhibit synergistic anticancer effect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ATS has anti-proliferation effects on human breast cancer [7], neuroblastoma [8] and ishikawa endometrial cancer [9]. HF also has the ability to inhibit the proliferation of human colorectal cancer cells [10], multiple myeloma cells [11], and liver cancer cells [12]. According to the history of using the formula of Qinghao and Changshan in TCM, we hypothesize that HF and ATS could exhibit synergistic anticancer effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the effect of HLF on colon cancer has been examined in the nude mouse (Chen et al, 2015), but its effects on TNF-, IL-2, IL-6 and IL-10 levels, ACF score, the main marker of colon cancer, PGM and TBARS levels have not been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HLF may induce apoptosis and reduce cancer volume in experimentally induced colon cancer in the nude mouse (Chen et al, 2015). It may also have antiangiogenic, antimetastatic and antiproliferative effects, increase apoptosis/necrosis, and decrease collagen content in other cancer types (Gavish et al, 2002;Grudzien et al, 2010;Jordan and Zeplin, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that halofuginone (HF) had a potent anticancer activity and slowed glycolysis via suppressing Akt/mTORC1 signaling and glucose metabolism. In HF-treated human colorectal cancer cells, there was a reduction in mTORC1 and phosphorylation of Akt, causing a rapid decrease in HK2 and Glut1 [66] . We recently found a novel role for eEF-2K, a negative regulator of protein synthesis, in promoting glycolysis and in tumor development and progression and the underlying molecular mechanism.…”
Section: Anti-cancer Therapy Based On the Warburg Effectmentioning
confidence: 99%